Assistant Professor, Department of Electrical Engineering, RIMT University, Mandi Gobindgarh, Punjab, India (International Journal of Innovative Research in Engineering & Management, 2021)
Acceptance and upkeep throughout the past two decades, the  beneficial features of cultural convergence of business  organisations have received a lot of attention. The challenges  and dangers that come with managing culturally diverse work  groups have not been properly addressed. There is a need for  practising managers to grasp when and when mono- and  multi-cultural organizations are best. This article analyses key  empirical findings that may be used to create effective cultural  diversity strategy paradigms in the workplace. The complexity  of an increasingly dynamic workplace require a search for  new methods to behaviour management. Traditional  paradigms that put an undue focus on production and  profitability may be inadequate to understand the complexity  of the future multi-cultural business. It would be a positive  step forward if greater emphasis is put on the growing trend  toward non-hierarchical, egalitarian, and flat organisational  structures. Above all, a community that welcomes and  appreciates the possibilities and challenges that come with a  diverse workforce is essential.
Keywords: Cultural Diversity; Diverse; Management; Minority; Majority; Organizations